2020
DOI: 10.1002/cam4.3680
|View full text |Cite
|
Sign up to set email alerts
|

A clinical model to predict distant metastasis in patients with superficial gastric cancer with negative lymph node metastasis and a survival analysis for patients with metastasis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Tumor size and TMN stage are significantly related to the survival of young gastric cancer patients (8). Many studies have proposed that age, race, tumor size, and depth may be risk factors for distant metastasis of gastric cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor size and TMN stage are significantly related to the survival of young gastric cancer patients (8). Many studies have proposed that age, race, tumor size, and depth may be risk factors for distant metastasis of gastric cancer (9).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high 5-year survival rate of T1 patients, many scholars have ignored the possibility of distant metastasis in T1 patients, especially in recent years when endoscopic treatment has gradually replaced traditional radical surgery 9 , 17 . A recent study showed that the probability of distant metastasis in patients with stage T1 is 8.17% 18 . Therefore, it is necessary to explore the risk factors and prognosis of distant metastasis of T1 gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The value of this index was consistent with our study. In general, a few studies have applied AUC to predict the OS 26 , 28 , 33 . The AUC values of ROC were more than 60% for 1-, 3-, and 5-year of survival, which are compatible with our study.…”
Section: Discussionmentioning
confidence: 99%